1991
DOI: 10.1099/00221287-137-1-15
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriolysis by Agaricus bisporus

Abstract: Agaricus bisporus, the cultivated mushroom, was able to mineralize dead 14C-labelled Bacillus subtilis and utilize the cellular components as sole source of carbon and nitrogen for growth. Consistently higher levels of bacteriolytic activity were obtained when A. bisporus was grown on lower concentrations of bacteria, 1.5 mg ml-1 as opposed to 3mg ml-1 basal liquid medium. A. bisporus also mineralized 14C-labelled bacteria in the presence of readily available alternative carbon and nitrogen sources such as glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Agaricus bisporus has been postulated to feed on compost bacteria since bacterial biomass was noted to decrease about fourfold during the cropping trial when analysing the phospholipid fatty acid content (Vos et al ., ). As reported, A. bisporus appears to degrade B. subtilis and was able to grow employing dead B. subtilis as the sole carbon and nitrogen source (Fermor and Wood, ; Fermor et al ., ). Thus, the bacteriolytic enzyme system produced by button mushroom may act as both a nutrient‐releasing system to obtain carbon, nitrogen and minerals, and as part of an antimicrobial system to protect the mushroom mycelium (Fermor et al ., ).…”
Section: Bioinoculants For the Mushroom Cropmentioning
confidence: 97%
“…Agaricus bisporus has been postulated to feed on compost bacteria since bacterial biomass was noted to decrease about fourfold during the cropping trial when analysing the phospholipid fatty acid content (Vos et al ., ). As reported, A. bisporus appears to degrade B. subtilis and was able to grow employing dead B. subtilis as the sole carbon and nitrogen source (Fermor and Wood, ; Fermor et al ., ). Thus, the bacteriolytic enzyme system produced by button mushroom may act as both a nutrient‐releasing system to obtain carbon, nitrogen and minerals, and as part of an antimicrobial system to protect the mushroom mycelium (Fermor et al ., ).…”
Section: Bioinoculants For the Mushroom Cropmentioning
confidence: 97%
“…A. bisporus is grown on mushroom compost which is composed mainly of lignocellulosic residues and microbial biomass (Wood & Smith 1987). It has been demonstrated that A. bisporus produces endoglucanases, cellobiohydrolases, b-glucosidases, cellobiose dehydrogenases, xylanases, mannanases, laccases, manganese peroxidases, which are involved in compost degradation (Wood 1989, Wood & Thurston 1991, Fermor et al 1991, Yagu¨e et al 1997. At present, four cellulose-growth specific genes have been isolated, cel1 (endoglucanase), cel2 (cellobiohydrolase), cel3 (cellobiohydrolase) and cel4 (mannanase) (Raguz et al 1992, Chow et al 1994, Yagu¨e et al 1997.…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial biomass nearly three-fold reduction, other fungi were dead ( Vos et al, 2017 ; Carrasco et al, 2020 ). The reduction of these bacteria and fungi is due to their degradation by button mushroom ( Fermor and Wood, 1991 ; Fermor et al, 1991 ). Therefore, the biomass of button mushroom largely derives from the degradation of other bacteria and fungi in compost.…”
Section: Discussionmentioning
confidence: 99%